Achieving Reproducibility and Closed-Loop Automation in Biological Experimentation with an IoT-Enabled Lab of the Future. (October 2018) - Miles, Ben; Lee, Peter L.
A robotic cloud laboratory driven by a state-of-the-art unified laboratory operating system integrates automated hardware, humans, and sensors. This lab of the future system enables researchers to transparently and collaboratively create, optimize, and organize biological experiments to achieve more reproducible results, perform around-the-clock experimentation, and more efficiently navigate the vast parameter space of biology.